2022
DOI: 10.3390/tropicalmed7050073
|View full text |Cite
|
Sign up to set email alerts
|

Needs Assessment of Southeastern United States Vector Control Agencies: Capacity Improvement Is Greatly Needed to Prevent the Next Vector-Borne Disease Outbreak

Abstract: A national 2017 vector control capacity survey was conducted to assess the United States’ (U.S.’s) ability to prevent emerging vector-borne disease. Since that survey, the southeastern U.S. has experienced continued autochthonous exotic vector-borne disease transmission and establishment of invasive vector species. To understand the current gaps in control programs and establish a baseline to evaluate future vector control efforts for this vulnerable region, a focused needs assessment survey was conducted in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Studies have shown the need for continued community and financial support for local MCPs to protect health [26][27][28]. Ideally, local MCPs would be consistently funded to support long-term and well-trained personnel experienced in routine and emergency mosquito control response [27]. Plans should be in place before a disaster occurs to mount an effective response [3,29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the need for continued community and financial support for local MCPs to protect health [26][27][28]. Ideally, local MCPs would be consistently funded to support long-term and well-trained personnel experienced in routine and emergency mosquito control response [27]. Plans should be in place before a disaster occurs to mount an effective response [3,29].…”
Section: Discussionmentioning
confidence: 99%
“…The National Association of County and City Health Officials (NACCHO) published a national Vector Control Assessment in 2020, finding that less than a quarter of mosquito and vector control programs in the US are "fully capable" regarding mosquito surveillance and control capacity (New Report Reveals State of Local Vector Control Capacity in the U.S. -NACCHO, n.d.). Additional regional and state vector control capacity surveys have reported similar results: the majority of mosquito and vector control agencies or programs are not prepared to handle major vector-borne disease outbreaks or are not proactive in various surveillance capabilities, leaving the US vulnerable (Dye-Braumuller et al, 2022;Moise et al, 2020;Peper et al, 2022). This vulnerability, in combination with anthropogenic climate change, urbanization, and international import and export, has set the stage for increased arboviral transmission in the US (Keyel et al, 2021;Wimberly et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…S. - NACCHO , n.d.). Additional regional and state vector control capacity surveys have reported similar results: the majority of mosquito and vector control agencies or programs are not prepared to handle major vector-borne disease outbreaks or are not proactive in various surveillance capabilities, leaving the US vulnerable (Dye-Braumuller et al, 2022; Moise et al, 2020; Peper et al, 2022). This vulnerability, in combination with anthropogenic climate change, urbanization, and international import and export, has set the stage for increased arboviral transmission in the US (Keyel et al, 2021; Wimberly et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Studies have shown the need for continued community and financial support for local MCPs to protect health [26][27][28]. Ideally, local MCPs would be consistently funded to support long-term and well-trained personnel experienced in routine and emergency mosquito control response [27]. Plans should be in place before a disaster occurs to mount an effective response [3,29].…”
Section: Plos Onementioning
confidence: 99%